A complete chloroplast genome of bamboo cultivar Phyllostachys edulis f. bicolor (Poaceae: Bambusoideae). Issue 4 (3rd April 2023) - Jing, Wenxuan; Hu, Bo; Wan, Rou; Guo, Qirong
Abstract: Phyllostachys edulis f. bicolor, a beautiful ornamental bamboo species, is a new variant of P. edulis, with yellow stems and green grooves between nodes. In this study, we assembled and annotated the complete chloroplast (cp) genome of this variety for the first time. The complete cp genome size of P. edulis f. bicolor was 139, 678 bp in length and a total of 130 unique genes were annotated, including 85 protein-coding genes, 37 tRNA encoding genes, and eight rRNA encoding genes. Phylogenetic analysis results provided evidence that P. edulis f. bicolor was closely related to P. edulis 'heterocycla'. This study contributes to better understanding of intraspecific type evolution of P. edulis .